2013
DOI: 10.1155/2013/130818
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Yoga and Stretching for Chronic Low Back Pain

Abstract: Although yoga is an effective treatment for chronic low back pain, little is known about the mechanisms responsible for its benefits. In a trial comparing yoga to intensive stretching and self-care, we explored whether physical (hours of back exercise/week), cognitive (fear avoidance, body awareness, and self-efficacy), affective (psychological distress, perceived stress, positive states of mind, and sleep), and physiological factors (cortisol, DHEA) mediated the effects of yoga or stretching on back-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 39 publications
3
71
1
Order By: Relevance
“…14 These results suggest that the effects of yoga on lower back pain may be due to stretching that occurs during asana, although both stretching and yoga may exert unique salutary effects as well. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 These results suggest that the effects of yoga on lower back pain may be due to stretching that occurs during asana, although both stretching and yoga may exert unique salutary effects as well. 29 …”
Section: Discussionmentioning
confidence: 99%
“…30 Thus yoga may provide the same psychological and physical benefits that other types of exercise do, as well as providing additional benefits, such as relaxation. 29 For example, a study of yoga in healthy participants in which investigators compared yoga to walking found that those in the yoga condition showed greater increases in positive mood and reductions in anxiety. 31 Investigators designed this study to test whether yoga adds to the known effects of physical exercise in improving mood and reducing anxiety, and carefully controlled for staff attention and interaction as well as energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on mediators of yoga and stretching for low back pain, physical factors were explored (including hours of back exercise per week), cognitive factors (including fear avoidance, body awareness and self-efficacy), affective factors (including psychological distress, perceived stress, positive states of mind and sleep) and physiological factors (including cortisol) [92]. The findings suggested that 36% of the pain reduction following 12 weeks of yoga was mediated by increased self -efficacy, 18% by sleep disturbance, 9% by hours of back exercise and 61% by a combination of the other factors.…”
Section: Potential Underlying Mechanisms For Pain Reduction Followingmentioning
confidence: 99%
“…We could identify key therapeutic mechanisms within these treatments by launching comprehensive and well-powered studies that incorporate multiple psychosocial chronic pain treatments and multiple mechanisms – a la Turner and colleagues -- to compare and contrast mechanism effects on outcomes, to assess timing of mechanism changes during treatment, and, importantly, to determine which techniques best engender mechanism changes. Indeed, some form of behavioral activation – physical exercise [16]; stretching [15] – may represent particularly potent techniques to achieve not only behavioral changes, but what may emerge as crucial cognitive changes (i.e., increased self-efficacy). Once critical mechanisms are identified, we can devote energy to improving techniques and processes that fully engage and maximize the impact of these factors, when to engage them during treatment, and which combinations of mechanisms should be engaged for maximum benefit.…”
mentioning
confidence: 99%